The Effect of Self-Efficacy on Leader–Member Exchange (LMX) Formation in Leadership Effectiveness - Kariuki, Josphat K. (International Leadership Journal, 2020)
A trivariate relationship between self-efficacy, leader–member exchange (LMX), and leadership effectiveness was established by eliciting the key traits of some supervisors and subordinate staff through open-ended interviews. A literature review verifies that self efficacy is central to leadership. Associated concepts such as self-awareness, self motivation, internal and external loci of control, and emotional intelligence are also investigated in this research. Their relationship with LMX behaviors and interactions between the leader and the followers are mapped. Individuals high in self-efficacy are seen to be high in LMX quality, resulting in effective leadership. This article contributes to the existing leadership knowledge with the finding that leaders and followers high in self efficacy have high-quality LMX, and therefore, a more effective leadership process between them.
Journal Article
Keywords: Leadership; LMX; Locus of control; Motivation; Self-Efficacy